KONFORMITAS SEBAGAI PREDIKTOR IMPULSIVE BUYING PADA DEWASA AWAL PENGGUNA GAME ROBLOX - Stefani Pandiangan; Yulia Fitriani; Fathana Gina (STKIP Subang, 2026)
This study is motivated by the increasing use of the online game Roblox, which not only serves as a form of entertainment but also as a social interaction space that may influence users’ consumptive behavior through virtual item purchases using Robux. This study aims to examine whether conformity can act as a predictor of impulsive buying among emerging adults who are Roblox users in community X. The research method used is a quantitative approach with a correlational design. The participants consisted of 231 emerging adults aged 18–25 years who are active Roblox users. Data were collected using a Likert-scale questionnaire consisting of conformity and impulsive buying scales, and were analyzed using simple linear regression analysis. The results showed a significant influence of conformity on impulsive buying with a significance value of p < 0.05. The coefficient of determination (R²) was 0.776, indicating that conformity explains 77.6% of the variance in impulsive buying, while the remaining percentage is influenced by other factors outside this study. In addition, the results also revealed a strong positive relationship between the two variables, meaning that higher levels of conformity are associated with higher levels of impulsive buying among Roblox users. Most respondents were also categorized as high in both conformity and impulsive buying, indicating a strong tendency to follow group influence in making virtual purchase decisions. In conclusion, conformity is proven to be a significant predictor of impulsive buying among emerging adults who use Roblox.